The cardiorespiratory response and physiological determinants of the assisted 6‐minute handbike cycle test in adult males with muscular dystrophy. Issue 3 (17th May 2018) - Morse, Christopher I.; Bostock, Emma L.; Twiss, Harriet M.; Kapp, Laura H.; Orme, Paul; Jacques, Matthew F.
ABSTRACT: Introduction : The assisted 6‐minute cycle test (A6MCT) distance was assessed in adults with muscular dystrophy (MD). Methods : Forty‐eight males, including those with Duchenne MD (DMD), limb‐girdle MD (LGMD), fascioscapulohumeral MD (FSHD), and Becker MD (BMD), as well as a group without MD (CTRL), completed handgrip strength (HGS), lung function [forced expiratory volume in 1 second (FEV1 ) and forced vital capacity (FVC)], body fat, and biceps thickness assessments. During the A6MCT, ventilation (VE ), oxygen uptake (VO 2 ), carbon dioxide (VCO 2 ), and heart rate (HR) were recorded. Results : A6MCT and HGS were lower in MD than CTRL subjects. FEV1, FVC, and biceps thickness were lower in MD than CTRL; lower in DMD than BMD, LGMD, and FSHD; but were not different between BMD, LGMD, and FSHD. A6MCT correlated with HGS, FEV1, FVC, body fat, VO 2, VCO 2, HR, and VE ( r  = 0.455–0.708) in pooled BMD, LGMD, and FSHD participants. Discussion : A shorter A6MCT distance in adult males with MD was attributable to HGS and lung function. The A6MCT is appropriate for assessment of physical function in adults with MD. Muscle Nerve 58 : 427–433, 2018